Small GTPase Rab3B: biological properties and possible role in carcinogenesis - A. A. Budko; P. A. Khesina; L. M. Diakov; N. L. Lazarevich (Успехи молекулярной онкологии)
Proteins of the superfamily of small guanosine triphosphate hydrolase (GTPase) perform various functions: from the control of cell proliferation to the regulation of vesicular transport. The superfamily of small GTPase Ras includes more than 150 proteins, devided to 5 major families (Arf, Ran, Rho, Ras and Rab), and plays an important role in carcinogenesis. Compared to the other families, the Rab family was investigated by relatively small number studies, which does not equally reflect their role in malignant transformation processes. In our review  we have focused on both the subfamily Rab3 and its poorly investigated member Rab3B. Recent findings allow to consider Rab3B not only  as a promising diagnostic or prognostic marker for several types of neoplasms, but also is a potential target for antitumor therapy. Our analysis of publicly available transcriptional databases revealed that kidney, lung and liver cancer patients with low Rab3B gene expression demonstrate a better overall five-year survival.